Materiali per lo studio del diritto antidiscriminatorio - FAVILLI, CHIARA; MONACO, MARIA PAOLA (Strumenti per la didattica e la ricerca, 2008)
Materiali per lo studio del diritto antidiscriminatorio is intended to provide a picture of most relevant legislation and jurisprudence in this sphere, at both European Union and national level. Divided into seven thematic sections - Sources, Gender, Age, Disability, Nationality, Race and ethnic origin, Religion and personal convictions - this collection sets up a direct comparison between European legislation and jurisprudence and the Italian enactment decrees. In this manner the editors, Chiara Favilli and Maria Paola Monaco, propose both to academics and to those working in the sector an innovative and useful instrument for combating discrimination on the grounds of gender, race, ethnic group, religion, age or sexual orientation.